Machine prepared thermoplastic polyurethanes of varying hard segment content: Morphology and its evolution in tensile tests. Issue 17 (10th May 2015) - Stribeck, Almut; Jokari‐Sheshdeh, Farhad; Pöselt, Elmar; Eling, Berend; in't Veld, Pieter J.; Goerigk, Günter Johannes; Hoell, Armin
ABSTRACT Machine‐cast thermoplastic polyurethanes are strained and monitored by small‐angle X‐ray scattering (SAXS). They are prepared from 4, 4′‐methylene diphenyl diisocyanate, 1, 4‐butane diol, and polytetrahydrofuran. Upon stretching hard domains are destroyed. Most stable are the domains of materials with a hard‐domain content (HSC) of 30%. Domain stability decreases with increasing HSC and crosslinking. Most materials show stability up to a strain 0.6. At higher strain, the apparent long period decreases for the materials with HSC = 30%. Correlated hard domains, the "strain probes" relax as others are destroyed. The fraction of relaxing probes and their ultimate relaxation decrease with increasing HSC. Chord distribution functions computed from the SAXS exhibit the same sequence of static long‐period bands. The band positions form a Fibonacci series, related to the underlying polyaddition process. This indicates a nearly quasicrystalline arrangement of stringed hard domains, identified as the strain probes of the discrete SAXS. At strains <0.6, the probes experience half of the macroscopic strain, which reflects hard‐domain rigidity. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2015, 53, 1213–1223